Academic and post-secondary participation of students with ABI after the BrainSTEPS program. Issue 3 (17th December 2022) - Riccardi, Jessica Salley; Eagan-Johnson, Brenda; Vaccaro, Monica; Ciccia, Angela H.
Abstract: Purpose: To describe and analyze educational and post-high school participation of individuals who sustained an acquired brain injury (ABI) during childhood and participated in a state-wide school-based brain injury support program, BrainSTEPS in Pennsylvania (BrainSTEPS). Method: Retrospective analysis of programmatic information and data collected through electronic and phone surveys during a follow-up survey for a statewide, school-based, school consultation program for students with ABI. Participants: Caregivers reported on 190 individuals with ABI who participated in Pennsylvania's BrainSTEPS Program. Results: Individuals post-ABI who participated in the BrainSTEPS were most likely to have experienced a mild ABI in high school due to sports. Post-injury, students were most likely to be enrolled in regular education, have graduated high school, pursued four-year college education and be attending post-secondary education and living with family. Additional significant relationships were not reported within the concussion or moderate-severe traumatic brain injury subgroups. Significant relationships for educational outcomes included higher likelihood of regular educational placement at the time of referral given an older grade at injury and regular educational placement before injury. For post-high school outcomes, a younger age at survey was associated with current attendance in post-secondary education, compared to other vocational options. Conclusions: Individuals with a history of ABI before school age and during primary and secondary education present with heterogeneous educational and post-high school outcomes. A greater breadth of measures of formal and informal educational and vocational supports and post-high school attainment should be implemented to accurately capture the needs and outcomes of these students to inform supports and services.